2021
DOI: 10.1021/acsapm.1c01626
|View full text |Cite
|
Sign up to set email alerts
|

Liquids that Freeze when Mixed: Homogeneous Cocrystallization Kinetics of Polyoxacyclobutane–Water Hydrate

Abstract: We report on the kinetics of crystallization of polyoxacyclobutane (POCB) and water to form a cocrystal hydrate, the first paper to explore the kinetics of crystallization of a polymer with a small molecule. POCB has unusual cocrystallization behavior when mixed with water, which could be exploited for a variety of applications including improving the nonvolatile memory storage capabilities of carbon nanotube devices, water purification, and biomedical applications such as drug delivery. The rates of hydrate c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(19 citation statements)
references
References 67 publications
3
15
0
Order By: Relevance
“…The above estimate of the salt fraction of 0.247 is an upper bound, since it assumes full crystallization of POCB, while polymers never crystallize to their full extent. In fact, we noted previously, 6,7 that in the absence of salt, the volume change of crystallization was approximately half of that expected for full hydrate crystallization. Thus, if we take χ = 0.5, eq 1 gives m 0.230 s Lw = , which is still relatively close to full saturation.…”
Section: ■ Results and Discussionmentioning
confidence: 71%
See 4 more Smart Citations
“…The above estimate of the salt fraction of 0.247 is an upper bound, since it assumes full crystallization of POCB, while polymers never crystallize to their full extent. In fact, we noted previously, 6,7 that in the absence of salt, the volume change of crystallization was approximately half of that expected for full hydrate crystallization. Thus, if we take χ = 0.5, eq 1 gives m 0.230 s Lw = , which is still relatively close to full saturation.…”
Section: ■ Results and Discussionmentioning
confidence: 71%
“…Even a few percent error in the published values of unit cell dimensions change the ρ c value, and hence the value of v c max significantly. 6 Next, we turn to the effect of salt on the crystallization rate. As in our previous studies 6,7 to quantify the kinetics, from each Δv c (t) curve, we identified the time τ at which the volume change reached 0.005 mL/g (chosen arbitrarily), i.e., Δv c (t = τ) = 0.005 mL/g.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations